IMPLEMENTASI NILAI-NILAI KARAKTER YANG TERKANDUNG DALAM KEGIATAN EKSTRAKURIKULER PRAMUKA SDN 18 PURNAMA KECAMATAN DUMAI BARAT - Sufriani, Ina; Saam, Zulfan; Caska, Caska (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
Character provides an overview of a nation, as a marker of characterization, as well as differentiating a nation from another. Character is the direction of how the nation will pass through an era and deliver it to a certain degree. A great nation is a nation that has character that is able to build a civilization of Saleh, (2012: 1). Character education which is systematically applied to one of the formal school institutions, namely Elementary School (SD) is a fairly good progress. The students acquire positive behaviors and habits that can increase their self-confidence. Character education applied to formal educational institutions can also be a means of civilizing and humanizing Noviani, (2011: 205-215). Data was collected through interviews, documentation and observation. Analysis of the data in this study with the following steps: Data Reduction, Data Presentation, Conclusion Drawing and Verification From the results of data analysis carried out on the impact of scouting activities in shaping the character of discipline and responsibility, namely rewards and punishments, direct orders and directions, and conditioning for every action. The achievement of 4 indicators of discipline and responsibility in keeping the lesson schedule such as doing the assigned tasks, discipline and responsibility in respecting time, students do not procrastinate on work, especially worship, self discipline and responsibility focusing on students' independence and discipline and responsibility in maintaining physical condition, namely students are able to maintain a healthy lifestyle.